Efeito do ácido cafeico e ácido cafeico fenetil éster em modelo de inflamação induzida por lipopolisacarídeo - Dalenogare, Diéssica Padilha (2016)
Peripheral inflammation is able to cause alterations in central nervous system (CNS) and lead to progression of neurodegenerative diseases. During neuroinflammatory process the activation of immune cells from the CNS and infiltration of peripheral immune cells occurs, which eventually release high levels of cytokines leading to oxidative stress. Lipopolysaccharide (LPS) is a biological active component of the membrane of gram-negative bacteria and is responsible for their toxicity being able to stimulate the immune system. This activation leads to increased expression of pro inflammatory cytokines such as interleukin 1β, IL-6, tumor necrosis factor (TNF-α) and production of reactive species. However, a large cell protection system is present composed of antioxidant enzymes such as glutathione antioxidant system and many other nonenzymatic antioxidants factors. Phenolic compounds have several functions, including antioxidant and anti-inflammatory function that can modulate and prevent damage caused by oxidative stress. Thus, it is intended to investigate the effect of treatment with caffeic acid (CA) and caffeic acid phenethyl ester (CAPE) on anti-oxidative stress and behavioral parameters in cortex of mice exposed to a systemic inflammatory model induced by LPS. The Swiss mice were divided into six groups: control (corn oil), control / CA 50 mg / kg, control/ CAPE 30 mg/ kg LPS 250μg / kg, LPS / CA 50 mg / kg LPS / CAPE 30mg / kg pre-treated orally by gavage during 30 days, both compounds were diluted with corn oil. After this period they were anesthetized, euthanized and the cerebral cortex removed for analysis. According to the results, we can observe the prevention of memory loss only in the animals of group LPS/CAPE 30mg / kg, and the other groups showed no significant difference in locomotor activity and memory. Regarding the oxidative stress parameters it demonstrated that LPS was able to increase the levels of reactive oxygen species, protein carbonyls and the levels of nitrite and nitrate. Already the AC and ACFE compounds showed protective effect on oxidative stress parameters developed by the injection of LPS in cortex samples, it was showing decreased levels of nitrite and nitrate, the protein carbonyls and levels of reactive species. In addition, AC and ACFE also showed a protective effect in maintaining glutathione system. Thus, it can be stated that both phenolic compounds, AC and ACFE exert antioxidant functions to forward oxidative damage developed by LPS injection in the CNS.